Why do immigrants have longer periods of unemployment? Swiss evidence. (18th December 2016) - Auer, Daniel; Bonoli, Giuliano; Fossati, Flavia
Abstract: Immigrant groups, especially those originating from non‐European countries, tend to experience disadvantages in the labour market and to be overrepresented among the recipients of welfare benefits in many European countries. In the public debate, this outcome is sometimes explained with reference to migration‐related factors such as weaker work values than natives (i.e., acceptability of remaining on benefits), smaller and lower quality of informal networks and lower levels of psychological well‐being. Indeed, we find that these factors significantly influence unemployment duration in the expected direction. However, they explain only a small share of the overall disadvantage that some immigrant groups experience. We conclude that at least some of the large differences we observed in unemployment durations are likely to be due to other factors including discrimination by employers.